Factors Influencing Social Entrepreneurial Intentions in the Context of the Jakarta Metropolitan City - Chandra, Felix Setia One; Wuisan, Dewi (Universitas Pelita Harapan, 2023)
This research aims to identify factors that influence social entrepreneurial intentions in the context of the metropolitan city of Jakarta. Specifically, this research examines the influence of empathy, moral obligation, self-efficacy, and social support on social entrepreneurial intentions in the context of the metropolitan city of Jakarta. Apart from that, this research also examines the influence of experience on social entrepreneurial intentions through the mediation of empathy, moral obligation, self-efficacy and social support. This research approach uses quantitative methods and data collection methods through electronic questionnaires using Google Form. The sample used as research data comes from business actors and employees of fashion MSMEs, who live in the city of Jakarta, Indonesia. The research conducted data analysis using the PLS-SEM method with research data originating from 160 respondents. Data analysis was carried out using the SmartPLS 4 application. The results of this research also prove that there is a positive and significant influence between empathy, moral obligation and self-efficacy on social entrepreneurial intentions. Then this research also obtained results that empathy, moral obligation, and self-efficacy mediate the influence of experience on social entrepreneurial intentions. Finally, this research found that the influence of social support on social entrepreneurship intentions and the mediation of social support on the influence of experience on social entrepreneurship intentions was not significant.